2006
DOI: 10.1007/s10887-006-9003-x
|View full text |Cite
|
Sign up to set email alerts
|

Dualism and cross-country growth regressions

Abstract: This paper develops empirical growth models suitable for dual economies, and studies the relationship between structural change and economic growth. Changes in the structure of employment will raise aggregate productivity when the marginal product of labor varies across sectors. The models in the paper incorporate this effect in a more flexible way than previous work. Estimates of the models imply sizeable marginal product differentials, and indicate that the reallocation of labor makes a significant contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 87 publications
2
78
0
5
Order By: Relevance
“…19 Dual economy models can be used to study this, and changes in the relative productivity of different sectors as development proceeds. There is long-standing evidence that structural change is associated with increases in the relative labour productivity of agriculture; see, for example, Temple and Woessmann (2006). Not all dual economy models readily generate this pattern, which makes it a useful test.…”
Section: Growth With Limited Geographymentioning
confidence: 99%
“…19 Dual economy models can be used to study this, and changes in the relative productivity of different sectors as development proceeds. There is long-standing evidence that structural change is associated with increases in the relative labour productivity of agriculture; see, for example, Temple and Woessmann (2006). Not all dual economy models readily generate this pattern, which makes it a useful test.…”
Section: Growth With Limited Geographymentioning
confidence: 99%
“…Esta característica facilita la implementación de la técnica en las economías en desarrollo y facilita la comparabilidad entre las economías desarrolladas y en desarrollo. Otra característica es que la técnica supone que no hay relaciones causales entre las variables (Temple y Woessmann 2006;Timmer y de Vries, 2009). Por tanto, la técnica no requiere ni puede distinguir entre las causas y las consecuencias de la terciarización.…”
Section: Análisis Shift-shareunclassified
“…A large body of empirical work establishes the significant role of educational level and quality in driving economic growth (Hanushek and Woessman 2008aand 2008b, Temple and Woessmann 2006, Barro and Sala-i-Martin 2004, Krueger and Lindahl 2001, Mankiw et al 1992, and Barro 1991. Studies have shown that student test scores on international assessments are positively related to economic growth (Hanushek and Woessman 2008).…”
Section: B Role Of Human Capital On Economic Developmentmentioning
confidence: 99%